Detlyrisk e jeg i Inventarium af Kaspar Kaum Bonnen og Altings A af Tomas Thøfner - Ølholm, Marianne (Folia Scandinavica Posnaniensia, 2007)
The poetic subject is a constituting feature of the poetic genre distinguishing it from other literary genres. The presence of a speaking voice and a central perspective in a poem is one of the most fundamental expectations to the poetic text, and it is a determining factor of the reader’s approach to the text as it offers the reader the possibility of understanding the poem through identification with the experiences and views of the speaking subject. As the genre evolves the poetic subject takes different forms, and in experimental postmodern poetry the lyric voice is often challenged and replaced by a fragmented expression favouring the polyphonic or impersonal. This paper examines the poetic subjects of two contemporary Danish works of poetry, Inventarium by Kaspar Kaum Bonnén and Altings A by Tomas Thøfner, and discusses the implications of the function of the poetic subject to the understanding of the text.